Pengaruh Modal Sosial Terhadap Kesuksesan Karir Manajer - Kistyanto, Anang (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
Abstract: This research aimed in explaining the influence of social capital toward career success. The design of this research was explanatory research. Using two stage sampling, the 232 questionnaires were distributed to the manager of state-owned companies (BUMN) at East Java and 108 of the questioner were returned. The result of structural equation model analysis showed that social capital affected toward career success. Keywords: social capital, social cliques, social network, trust, norms of resiprocity, career success